Meeting the stakeholder needs and sustaining business through sustainability risk management practices: A case study of Malaysian environmentally sensitive companies - Abdul Aziz, Nazliatul Aniza; Abdul Manab, Norlida (Springer, Singapore, 2019)
Sustainability issues such as climate change, carbon emissions, and energy consumption have become increasingly important issues among business organisations, academics and policy makers. Considering this complexity, stakeholders currently demanding companies to have a sound risk management that are aligned to their interest. Sustaining business requires a strong foundational on the economic, environmental and social aspects to address risks and capture value. Sustainability risk management (SRM) is a process that systematically integrates environmental, social, and economic aspects to address emerging risks and other non-quantifiable risk for company survival. This study aims to examine the impact of SRM practices on the company survival among the environmentally sensitive companies in Malaysia. A case study was carried out to examine the SRM implementation among the environmentally sensitive companies. The finding shows that leadership and compliance are considered as important factors in implementing SRM programme. Other factors such as sound risk culture, adequate risk management tools, and effective business continuity planning are crucial to support SRM implementation. Overall findings revealthat the companies are at the early stage implementing SRM programme and denote there is much room for improvement in the risk management process to create long-term value creation for the stakeholders. This study provides empirical evidence on the significance of SRM factors to the company survival. Given the huge environmental and social costs arising from sustainability issues, companies should intensify their effort to fully implement SRM programme across the organisation to sustain longer.